Relationship between Family Support and Health Personnel with Labor Preparedness in Pregnant Women in Hospitals - Santi Sumaryanti; Grace Carol Sipasulta; Rahmawati Shoufiah (Indonesian Journal of Sport Management and Physical Education, 2023)
Birth readiness needs support from family and health workers. Family support and health workers have an effect on increasing knowledge and preventing an increase in the Maternal Mortality Rate. This study discusses the support of families and health workers in preparing for childbirth, which is still very small. This study aims to determine the relationship between family support and health workers on delivery readiness in pregnant women. The population was third trimester pregnant women, a total sample of 95 respondents according to the inclusion criteria for third trimester pregnant women were hospitalized. Patient data is normally distributed. The results of the Chi-Square test of family support and readiness for childbirth are p-value 0.000 <α 0.05, there is a relationship between family support and readiness for childbirth in pregnant women, good support 49 mothers are more prepared for childbirth, lack of family support, 41 mothers are not ready . Support of health workers with readiness for delivery p-value of 0.000 <0.005 there is a relationship between the support of health workers and readiness for delivery in pregnant women, receiving the support of 48 mothers who were not ready for childbirth. lack of support from health workers, 38 mothers were not ready for childbirth. Family support and health workers need to be increased in providing better birth readiness for pregnant women